1996
DOI: 10.1021/ma9603140
|View full text |Cite
|
Sign up to set email alerts
|

Theory of Polymer Brushes of Liquid-Crystalline Polymers

Abstract: Liquid crystalline ordering in polymer brushes formed by macromolecules with mesogenic groups in the main chain and immersed in a solvent is investigated theoretically by numerical calculations within a self-consistent field approximation. Existence of a microphase-segregated brush regime with a collapsed orientationally ordered intrinsic sublayer and a swollen external sublayer is shown. At high grafting density (σ), the transition from a conventional brush state to the microphase-segregated state is continuo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
93
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 43 publications
(97 citation statements)
references
References 13 publications
4
93
0
Order By: Relevance
“…16,17) , the first order phase transition in a point U B = U B tr remains so. However, the jumb of density for a brush as a whole is substituted by a jump in a thin sublayer with higher u p value.…”
Section: Note Added In Proofmentioning
confidence: 90%
“…16,17) , the first order phase transition in a point U B = U B tr remains so. However, the jumb of density for a brush as a whole is substituted by a jump in a thin sublayer with higher u p value.…”
Section: Note Added In Proofmentioning
confidence: 90%
“…According to theoretical simulations, the main factors determining the orientational and conformational properties of macromolecules in brushes are density of their grafting, molecular weight of polymer used and outer conditions. [2][3][4] Among the approaches allowing to optimize these parameters there is a change of chemical structure of spacer used for grafting polymer moieties to the surface.…”
Section: Introductionmentioning
confidence: 99%
“…[11] In another study simple analytical solutions for the SCF potential were found assuming a brush consisting of chains of finite extensibility, which are free walks on simple cubic, diamond and body-centered cubic (BCC) lattices. [12] The solution for a brush on the BCC lattice is more convenient for investigations. For brevity we call the model of a brush on the BCC lattice BCC model.…”
Section: Introductionmentioning
confidence: 99%
“…An analytical solution was found for density profiles r(x) and free-ends distributions g(y) for the BCC model in a good solvent. [12] The analytical solution of a salt-free polyelectrolyte BCC model in a good solvent is also described. Investigations into polyelectrolyte brushes with finite extensibility was also described.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation